Estimation of Runners' Lactate Threshold Heart Rate and Speed by Heart Rate Variability - Lu, Changda; Lu, Siyu; Wu, Yiwei; Xing, Qingjun; Pan, Bingyu; Shen, Yanfei (International Journal of Sports Medicine)
Accurate measurement of training intensity is crucial for optimizing endurance running performance. Lactate Threshold Heart Rate (LTHR) and Speed (LTspeed) are commonly used but require invasive, costly methods. Heart Rate Variability (HRV) metrics offer a non-invasive alternative by assessing autonomic nervous system activity. This study evaluated the validity of various HRV metrics in predicting LTHR and LTspeed during indoor and outdoor graded exercise tests (GXTs) in 19 recreational runners. HRV thresholds (HRVTs) were determined using SD1, SD2, DFA-α1, DFA-α2, SDNN, and RMSSD via the Dmax method, and are referred to as HRVT1 to HRVT6. Indoor GXT results showed HRVTHR often underestimated LTHR, with all HRVTs, except HRVT4speed (DFA-α2, p = 0.06), showing significant differences from LT. Moderate correlations were observed for HRVT5HR (SDNN, r = 0.66), HRVT2speed (SD2, r = 0.56), and HRVT3speed (DFA-α1, r = 0.70). Outdoor GXTs showed no significant differences between most HRVTs and LT, except HRVT6HR (RMSSD, p = 0.03). HRVTspeed demonstrated moderate correlations (r = 0.54–0.7) with LTspeed. While HRVT and LT may reflect different physiological thresholds, HRVTs, particularly those based on DFA-α2, show promise as non-invasive predictors of LT in recreational runners.